(3GdGYJQGaGJ HbQGQGJ GdJMcje GdCLfHjI h GfbGPgG (B/s - (3GdLfHjgi, efjQ eMeOs; (3GdLfHjgj, eeOhM eMeO s ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2005)
(3GdWQb GdHOjdI daV GdefGRYGJ, GdGee GdeJMOI , GdLeYjI GdYGeI, JbQjQ GdaQjb Gdafj GdYGed GdeYfj HGdJMcje , bHhd COdI eYjfI aj GdGLQGAGJ GdbVGFjI Ch GdJMcjejI GdGMbI, OhQ Gdehab aj GdGLQGAGJ GdJMcjejI Ch GdbVGFjI , GJaGb GdJMcje GdcJGHj h GdJLGQI GdOhdjI , GTJQGW GdTQW GdcJGHj dGJaGb GdJMcje , GJaGbjI GdGee GdeJMOI HTCf GdGYJQGa HbQGQGJ GdJMcje GdGLfHjI h GfaGPgG , GdGJaGbjI GdYQHjI HSCf GdbhGYO h GdGLQGAGJ GdJj JMce JShjI GdefGRYGJ , GdGYJQGa HbQGQGJ GdJMcje GdOhdjI h GfaGPgG WHbG dbGfhfGdJMcje GdJhfSj , GdJJMcje GdShQj , GdJMcje GdYqeGfj , GdJMcje GddHfGfj , GdJMcje GdeUQj h GdJMcje Gdjefjs
Keywords: (3GdJMcjes; (3GdJMcje GdOhdjs